Debating Transformations of National Citizenship (IMISCOE Research Series,, 2018)
This open access book discusses how national citizenship is being transformed by economic, social and political change. It focuses on the emergence of global markets where citizenship is for sale and on how new reproduction technologies impact citizenship by descent. It also discusses the return of banishment through denationalisation of terrorist suspects, and the impact of digital technologies, such as blockchain, on the future of democratic citizenship. The book provides a wide range of views on these issues from legal scholars, political scientists, and political practitioners. It is structured as a series of four conversations in which authors respond to each other. This exchange of arguments provides unique depth to current debates about the future of citizenship. .